Diagnóstico de la formación académica del Zootecnista y la relación con su desempeño profesional en el Departamento de Antioquia - Galeano Vasco, Luis Fernando; Vélez, Carlos A.; Gaviria, Carolina (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In the process of the curricular restructuring of the Zootechny program a research on the current state of the academic training of the Zootecnician and it´s relation to the professional performance was carried out by means of direct person to person surveys with multiple answer and excluding type questions, distributed within the thematics of: 1) assesment of the usefulness of the knowledge obtained in the undergraduate program for the professional performance, which presented a minimum usefulness (45.16%), partial usefulness (26.88%) and total usefulness (25.81%); 2) evaluation of the curricular plan consisting of 40 subjects, distributed in the basic and professional areas and qualified by the respondents as follows: Universidad de Antioquia (UdeA): Fundamental (27.87%), Pertinent (80.33%) and to be changed (8.20%); Universidad Nacional Sede Medellín (UNM): Fundamental (73.77%), Pertinent (36.07%) and to be changed (13.11%); Other Universities (OU): Fundamental (5.46%), Pertinent (52.46%) and to be changed (16.39%); 3) Enphasis on the training in husbandry systems: Cattle (29.01%), Porcine (21.84%) and Aviary (14.51%); 4) Complementary studies, post-degree: Masters (56.67%), specializations (36.67%) and PhDs (6.67%); and in non formal education in the seminar category (38.61%), Diplomas (17.82%) and short courses (27.72%). The survey area was limited within the geographical Metropolitan Area of Medellín, Antioquia. The information used a statistical model comprised of a multiple answer, chi-square independence analysis and a statistical description of the data using SPSS 14.0 software, performed by the group INCEMA of the Universidad de Antioquia.